Website service quality, perceived value, trust, convenience and customer loyalty of online shopping - Noorashikin, Harun@Che Ani (2014)
As the Internet has matured, there has been a huge growth in the volume and value of online transaction. Furthermore, it becomes a common channel for delivering and trading of information, products and services at global marketplace. Even though this method of business exchange or transaction has started to win the hearts of Malaysian users, the main elements influencing the willingness and retentions to purchase online are still unknown. Thus the objectives of this study is to identify the relationship between customer loyalty with other independent variables such as website service quality, perceived value, trust and convenience in online shopping transactions A total of 200 academic lecturers in Politeknik Sultan Abdul Halim Mu'adzam Shah were responding to this study Further, Statistical Package software for Social Science (SPSS) Version 20.0 was used to analyze the collected data. Descriptive statistic, factor analysis and correlation were applied to this study The results of this study were clearly shown that the independent variables (website service quality, perceived value, trust and convenience) had positive impact on dependent variable (customer loyalty in online shopping). It is suggested for future research to conduct this type of research and to be extended to any other countries in order to determine consumer pattern in online shopping behavior. Moreover, future research also should focus on differentiation of consumer's behavior in term of products, websites also the industries